Girard y Nietzsche: el asesinato de colectivo de Dios - Barahona Plaza, Ángel Jorge (Cauriensia, 2023)
Girard says that Nietzsche is a great theologian. He thinks that the discovery of the death of God, product of a collective murder of the human mass, is something more than a brilliant intuition. It reveals the founding mechanism of human culture and, at the same time, the role played by Christianity, that consummates that first intuition in the Passion of Christ. But if on the one hand Nietzsche identifies the death of Dionysus with the death of Christ, on the other Girard will say that there is a great difference in their respective meaning. The first perpetuates the eternal return of the same, typical of archaic religions, while the death of Christ inaugurates an unprecedented novelty in history: it de-divinizes the victims.